Application Of Maqasid Al-shariah In Responsible Investment (msri) And Practices Towards Esg - Nur Ainna Ramli; Fauzias Mat Nor; Muhammad Ridhwan Ab. Aziz; Syahidawati Hj. Shahwan; Ainulashikin Marzuki; Mohamad Yazis Ali Basah; Hisham Sabri (EnPress, 2024)
Non-Indexed Publication